The challenge for a historically disadvantaged South African university to produce more postgraduate students - Sonn, R (South African Journal of Higher Education, 2016)
There is a shift in emphasis in higher education from producing bachelor’s degrees en masse to an increase in the production of graduates with post-graduate qualifications. In recent times more and more universities in South Africa place emphasis in recruiting students doing post-graduate degrees and encourage them to complete their research component of their studies in the stipulated time in order to increase the subsidy received from the Department of Higher Education and Training (DHET) and the research output of students and staff. For WSU, this issue is relatively crucial, given its low throughput rate of post-graduate students. This paper in particular draws from a research study conducted with B Ed (Hons) and M Ed students at WSU Ibika Site to establish the challenges they experienced in doing their research. The students usually finish their course work in record time, but find it very difficult to complete the research component of the programme. The result is that there are a number of students in the system. This qualitative study explored the challenges faced by these students in completing the research component of their respective programmes. A purposive sample of 20 students were selected to participate in the study. Interviews were conducted to collect the data. Ethical considerations were employed. Content analysis was used to analyse the data. Some of the challenges experienced by the participants included, inter alia, problems experienced in identifying the problem statement; the complexity of proposal writing; a lack of professional writing skills; etc. Based on the findings of the study the author provided some recommendations. KEYWORDS: resource-based economy; knowledge-based economy; post-graduate studies; problem statement; proposal writing; supervisor.